A qualidade do relacionamento conjugal e o desempenho social de crianças pequenas - Machado, Fabiana Rocha (2009)
The scientific literature indicates that certain family characteristics can act as risk factors for children s social development, such as low income and low educational attainment levels, adolescent pregnancy, social isolation, parents who are highly stressed, single-parent families, a parent with a psychiatric disorder (including depression), parents with a criminal history, a history of drug abuse, or a high-conflict spousal relationship. More detailed information about some of these factors is lacking, particularly with respect to the Brazilian context, as in the case of spousal conflicts. Such information is essential to permit the construction of preventive programs that could reduce risk factors for infant social development, in Brazil. Risk factors can contribute to the development of problem behaviors among children and, as a result, interfere in their social relationships, as well as contributing to other difficulties such as learning problems, depression, anxiety and other psychological conditions. For this reason, the identification and prevention of risk factors that can harm human development is one of the research areas of the Special Education Graduate Program at the Federal University of São Carlos (Brazil). Although the number of Special Education prevention programs has increased significantly, especially in the United States, there are few prevention programs in this area, in Brazil, resulting in a situation in which professionals face the difficult task of remediating long-term problems. Considering the paucity of Brazilian studies that aim to verify the impacts of conflicts in the spousal relationship on infant social development, particularly among very young infants, the objective of this study was to investigate the relationships between personal parent-characteristics, characteristics of the spousal relationship and the social performance of their child, between one and two years of age. Given the exploratory nature of this study, a non-experimental design was used. Participants included 27 couples and their target child, who was between 15 and 26 months of age and who attended a daycare center in the city of Araraquara, São Paulo, Brazil. The parents completed an instrument to evaluate their socioeconomic situation, a Marital Social Skills Inventory, a Description of Conflict Situations, and Lipp s Adult Stress Symptoms Inventory. The Operationalized Portage Inventory was used to evaluate the children s social performance. Although there was a certain amount of variability in the participants responses, the correlations between the parents personal characteristics and their child s social performance were non-significant. With respect to the parents marital social skills, in this sample, there was a significant negative correlation between the frequency with which the parents reported that they stomped out of the room, and the child s social performance (r = - 0.48, p < 0.05). Using the results from this study together with those from other studies about this topic, it should be possible to create programs that can help prevent problems in families with children in this age group, striving to provide them with the means to transform some of the characteristics of their spousal relationship so that they will be protective factors for their child s development.